An Evalution of the Demographic and Clinical Characterictics of Patients with GM2 Gangliosidosis - Esra Er; Ebru Canda; Havva Yazıcı; Cenk Eraslan; Eser Sözmen; Sema Kalkan Uçar; Mahmut Çoker (Galenos Yayinevi, 2018)
Aim:The purpose of our study is to submit the demographic, phenotypic and age at diagnosis characteristics of children with GM2 gangliosidosis.Materials and Methods: Patients with GM2 gangliosidosis who were referred to Ege University Faculty of Medicine, Department of Pediatrics, Division of Pediatric Nutrition and Metabolism between January 2004 and December 2016, were included in this study. Diagnosis was confirmed by determining the level of serum β-hexosaminidase activity and genetic mutation analysis. The demographic and clinical features are reported for 8 patients with Tay-Sachs disease (TSD) and 6 with Sandhoff disease.Results:The mean age at diagnosis was 18.2 months (range 4-48 months) and 14.5 months (range 8-36 months) for patients with TSD or Sandhoff disease respectively. The initial and main complaint in 100% of the patients were neurological disorders, such as developmental delay, developmental regression or both; seizures and macrocephaly. None of the patients exhibited evidence of organomegaly. Cranial magnetic resonance imaging results were normal in 36% of the cases, 55% of the cases had bilateral thalami involvement presenting as T2 hyperintensity especially at the posterior thalami and 9% of cases had myelination delay.Conclusion:GM2 gangliosidosis disease should be considered for children with developmental regression and/or delay. To prevent a delay in diagnosis, β-hexosaminidase activity in serum and genetic mutation analysis should be undertaken in suspected cases. Curative gene therapy may be available in the future.